Virgin Coconut Oil Meningkatkan Aktivitas Fagositosis Makrofag Ayam Pedaging Pascavaksinasi Flu Burung (VIRGIN COCONUT OIL INCREASES THE PHAGOCYTOSIS ACTIVITY OF MACROPHAGE OF BROILER CHICKEN FOLLOWING AVIAN INFLUENZA VACCINATION) - Yuniwarti, Enny Yusuf Wachidah; Asmara, Widya; Artama, Wayan Tunas; Tabbu, Charles Rangga (Jurnal Veteriner; Vol 14 No 2 (2013), 2013)
The research objective was to find an alternative avian influenza prevention in broilers by increasinganimal’s antibody titer and macrophages phagocytic  activity.  Virgin coconut oil (VCO) is a food supplementthat is proven safe for human consumption therefore it is assumed to be safe for the animal’s (chickens).Factorial design  2 vaccinated: unvaccinated) x 4 (dose of VCO: 0, 5, 10 and 15 mL/kg feed) were applied inthis study.  A total of 40 day day old chick were allocated in the eight treatments groups.  Feed and drinkingwater were available  ad libitum.  Antibody titers of the animals were detected using ELISA, whereasphagocytic activity of the macrophages were detected from spleen.  The result showed that the highestphagocytic activity and antibody titers were seen in chickens which were given VCO at 10 mL/kg feed.  It isconcluded that the VCO could increased the phagocytic activity of macrophages.
Keywords: avian influenza, phagocytic activity, macrophage, broiler chicken,VCO